Germline mutations in ETV6 are associated with thrombocytopenia, red cell macrocytosis and predisposition to lymphoblastic leukemia. - Noetzli, Leila; Lo, Richard W; Lee-Sherick, Alisa B; Callaghan, Michael; Noris, Patrizia; Savoia, Anna; Rajpurkar, Madhvi; Jones, Kenneth; Gowan, Katherine; Balduini, Carlo L; Pecci, Alessandro; Gnan, Chiara; et al. (Nat Genet, 2015)
Some familial platelet disorders are associated with predisposition to leukemia, myelodysplastic syndrome (MDS) or dyserythropoietic anemia. We identified a family with autosomal dominant thrombocytopenia, high erythrocyte mean corpuscular volume (MCV) and two occurrences of B cell-precursor acute lymphoblastic leukemia (ALL). Whole-exome sequencing identified a heterozygous single-nucleotide change in ETV6 (ets variant 6), c.641C>T, encoding a p.Pro214Leu substitution in the central domain, segregating with thrombocytopenia and elevated MCV. A screen of 23 families with similar phenotypes identified 2 with ETV6 mutations. One family also had a mutation encoding p.Pro214Leu and one individual with ALL. The other family had a c.1252A>G transition producing a p.Arg418Gly substitution in the DNA-binding domain, with alternative splicing and exon skipping. Functional characterization of these mutations showed aberrant cellular localization of mutant and endogenous ETV6, decreased transcriptional repression and altered megakaryocyte maturation. Our findings underscore a key role for ETV6 in platelet formation and leukemia predisposition.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Erythrocytes, Abnormal; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Germ-Line Mutation; HEK293 Cells; Hematologic Diseases; Humans; Male; Mutation, Missense; Pedigree; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Proto-Oncogene Proteins c-ets; Repressor Proteins; Thrombocytopenia

MYH9-related disease: a novel prognostic model to predict the clinical evolution of the disease based on genotype-phenotype correlations. - Pecci, Alessandro; Klersy, Catherine; Gresele, Paolo; Lee, Kieran J D; De Rocco, Daniela; Bozzi, Valeria; Russo, Giovanna; Heller, Paula G; Loffredo, Giuseppe; Ballmaier, Matthias; Fabris, Fabrizio; Beggiato, Eloise; et al. (Hum Mutat, 2014)
MYH9-related disease (MYH9-RD) is a rare autosomal-dominant disorder caused by mutations in the gene for nonmuscle myosin heavy chain IIA (NMMHC-IIA). MYH9-RD is characterized by a considerable variability in clinical evolution: patients present at birth with only thrombocytopenia, but some of them subsequently develop sensorineural deafness, cataract, and/or nephropathy often leading to end-stage renal disease (ESRD). We searched for genotype-phenotype correlations in the largest series of consecutive MYH9-RD patients collected so far (255 cases from 121 families). Association of genotypes with noncongenital features was assessed by a generalized linear regression model. The analysis defined disease evolution associated to seven different MYH9 genotypes that are responsible for 85% of MYH9-RD cases. Mutations hitting residue R702 demonstrated a complete penetrance for early-onset ESRD and deafness. The p.D1424H substitution associated with high risk of developing all the noncongenital manifestations of disease. Mutations hitting a distinct hydrophobic seam in the NMMHC-IIA head domain or substitutions at R1165 associated with high risk of deafness but low risk of nephropathy or cataract. Patients with p.E1841K, p.D1424N, and C-terminal deletions had low risk of noncongenital defects. These findings are essential to patients' clinical management and genetic counseling and are discussed in view of molecular pathogenesis of MYH9-RD.
Keywords: Adult; Age of Onset; Amino Acid Substitution; Cataract; Female; Genetic Association Studies; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Linear Models; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Phenotype; Risk Factors; Thrombocytopenia